İsrail-Filistin Savaşının Küresel Medya Temsiline Karşı İkna Edici Bir Araç Olarak Veri Görselleştirme/Hikâyeleştirme: Visualizing Palestine Örneği. - Cayık, Selim (Journal of Media & Culture / Medya ve Kültür)
This study analyzes the hegemonic structure of the pro-Israeli discourse that emerged in global media after October 7, 2023, and examines data visualization/storytelling practices as an alternative narrative form developed against this representation. The research focuses on the Visualizing Palestine platform as a case study and analyzes the persuasive power of its data-based visuals through Aristotle’s rhetorical components-ethos, logos, and pathos. The theoretical framework of the study is grounded in Gramsci’s concepts of hegemony and counter-hegemony, along with Stuart Hall’s model of representation and encoding/decoding. The findings reveal that Western-centered global media present the Palestinian issue through a narrative that frames October 7 as the "beginning," thereby legitimizing Israel’s colonial policies. In contrast, Visualizing Palestine reverses this narrative by making the historical context visible through data-driven and emotionally engaging visuals. These visualizations produce a counter-hegemonic rhetoric that transforms the audience from passive observers into ethical witnesses. The study demonstrates that data visualization is not only an informative but also a transformative and political mode of expression. Consequently, the example of Visualizing Palestine shows that data-driven narratives in the digital age function as ethical, aesthetic, and epistemological tools of resistance against global media representations.